Implementación de un aplicativo web para la gestión de la información de la cooperativa de transportes interprovincial de pasajeros La Maná en el cantón La Maná en el año 2017. - Tayopanta Masabanda, Segundo Olger (2018)
The organizations in these new moments seek to be linked to the new advances that the technologies have been experiencing, in this way, it is important to mention that the research which was developed has many positive aspects in the field of information management, so that; the object of study was the Cooperativa de Transporte Interprovincial de Pasajeros "La Maná", where a web application was implemented with the idea of improving the processes that are carried out in an inappropriate manner, among which the following can be mentioned: the agglomeration of users looking for a seat is permanent, because there is no automatic registration of available seats, users are unaware of the different routes of buses and do not know what bus is available for a particular sector, facing the problems that were identified the aforementioned application will allow the different users to make the reservation of the seats through the internet, and avoid inconveniences to managers, administrators and users. As fundamental elements for the proposed development, the following considerations were taken into account: in the first instance, the requirements were surveyed to meet the needs of the users, which was obtained by applying the respective interviews and case studies to those involved, for storage of data we used a database manager such as MySQL that provides the following benefits, speed in performing operations, which makes it one of the managers with better performance, low cost requirements for the development of databases, since due to its low consumption it can be executed in a machine with scarce resources without any problem, easy configuration and installation, it supports a great variety of Operating Systems, low probability of corrupting data, even if the errors do not occur in the manager, Netbeans was also used because it is ideal to work with the language of JAVA development, as well as offering an excellent environment to program in PHP, as a programming tool this PhP is a very popular open source language especially suitable for development web and that can be embedded in HTML, the MVC framework was also used because this Codeigniter is a framework for the development of applications in PHP that uses the MVC. It allows Web programmers to improve the way they work and to do it at a higher speed, as a software development methodology the Scrum agile methodology was applied because it is a process in which a set of good practices are applied on a regular basis to work collaboratively, as a team, and obtain the best possible result of a project. The installation and execution of the web system will be done on a computer that serves as a remote web server under the Ubuntu Mate operating system, the use of a public IP will be made. The software evaluation will be carried out by means of white and black box tests to detect existing errors and provide a solution.